Mania as Debut of Cushing’s Syndrome - Ricardo Álvarez Martínez; Rosa María Tomé Rodríguez; María Álvarez Ariza; Carlos Spuch; Jose M. Olivares (Case Reports in Psychiatry)
This is a case of a patient affected by Cushing syndrome that was admitted at the hospital due to hormonal problems. He had presented psychiatric symptoms that were mistakenly considered not directly connected to the pathology causing the clinical condition, but a mere psychological reaction to it.